Immersive Learning: Transforming Financial Education Through Virtual And Augmented Reality Technologies - Bouguetaia Soufyane; Mellah Adda (جامعة الوادي University of Eloued, 2024)
This paper explores the transformative potential of virtual reality (VR) and augmented reality (AR) in financial education. It delves into various case studies and examples, showcasing how VR and AR technologies are revolutionizing financial learning. These include VR-based trading simulations in universities and AR apps for financial literacy. The paper discusses the advantages and challenges of implementing VR and AR, emphasizing improved engagement, personalized learning, and real-world application of financial concepts. Recommendations are provided for educators, policymakers, and industry stakeholders to leverage these technologies effectively. The conclusion underscores the need for greater investment and collaboration to advance innovative financial education initiatives using VR and AR.
Keywords: virtual reality; augmented reality; financial education; financial literacy; technologies